CHALLENGES FOR HIGHER EDUCATION AND THEIR SOLUTIONS - Mishra, Prince Kumar; Paney, Krishna Kumar (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Today in this competitive world education is most important and to be in higher position or in upper post the value of education has increased. Correct education makes way for achieving each and every goal. Education increases our area of knowledge, and also makes us mentally strong. Every child is having its aim likewise their parents are also having desires that their kids grow and get educated to become a doctor, an engineer, IAS officer and so on. To fulfil all the dreams and desire there is only one way and i.e. Higher education. To become successful in life and fulfil once dreams and desire education is most important and plays a major role in achieving those goals. Education is the only key to every lock of those doors which opens to achieve our dream. Knowledge acquired during the whole educational process make the person strong it act as a spinal cord in person’s life. By saying this we can understand the importance of higher education and the knowledge and skills acquired by that. For the better future of young India government has launched many schemes and projects so, that the needs of today’s generation and developing India can be reached. So, to be in the topmost position and to make India in first position in world there is need of changes and addition of new things to the higher education for that various approaches has been made and a lot more things are added per day.